Gender policies and the economy of dispossession in rural habitability in the Aconcagua Valley - Rodó-Donoso, Francisca (2024)
Introduction: This article presents concerns about the current characteristics of rural territories, the transformations caused by agroextractivist and developmentalist policies in the Aconcagua Valley. Objective: The objective of the research is to make visible the impact on the environment, incorporating public policies and national programs that place women as recipients of strategies to face transformations in rurality, which evidences conflicts linked to the sustainability of life. Methodology: The methodology is an embodied and collaborative ethnography, carried out with women's groups in Pullalli and Olmué, with whom workshop sessions were held using body mapping, body-earth and life history techniques. Open interviews were also conducted with key actors in the Aconcagua Valley. Conclusions: The findings discuss the dispossession of water and the economic tensions on women's bodies and territory based on the neoliberal economic model, intersecting patriarchal and colonial elements in rurality. This threatens human and non-human life from a collective interdependence approached. It concludes that rural transformations are entrenched, which has changed the way in which women collectively deploy strategies for the reproduction of life.